Processing of date palm kernel (DPK) for production of nutritious drink - Mirghani, Mohamed Elwathig Saeed (American-Eurasian Network for Scientific Information (AENSI), 2012)
Date palm kernel (DPK) is a solid waste of date’s industry and date consumption. Kernel is about 12 -15% of the date (wt/wt) so if the world production is more than 7 (seven) million metric tons; the kernels (seeds) shall be about one million metric tons that almost consider waste. This research studied the potential of producing a nutritious drink from DPK. The DPK powder was analyzed for nutritional compounds that resulted in protein 0.99 mg/g, glucose 0.74 g/L fructose 0.6 g/L and anther traces of simple sugars. Analysis of mineral elements in the ash showed the average values of Cu, 0.92 mg/L; Ca, 2.04 mg/L; Fe, 0.91 mg/L; Mn, 0.43 mg/L; Mg, 4.99 mg/L and K, 6.74 mg/L. Factorial design was used for optimization with three independent variables, which were the volume of water, amount of sucrose and citric acid. The maximum overall acceptability through the sensory evaluation test was achieved for the DPK drink formulation of 150 mL water, 30 g sucrose and 4.0 g citric acid. Analysis of the results was evaluated using Design-Expert (DX6) software by statistical tools.